Factors contributing to commitment to change among outcome based budgeting focal person in government ministries in Malaysia - Afizal, Kasa (2020)
Due to rapid changes in technology, the evolution of open economy and the need to fulfil public expectations within limited resources, the Malaysian Public Sector has undergone a lot of reform initiatives with the objective to increase its efficiency and effectiveness. Outcome Based Budgeting (OBB) was introduced in 2010 as part of the public finance reform in Malaysia public sector. However, based on the number of studies, Malaysia is experiencing only a small progress particularly in measurement of outcome which is the core component in performance budgeting. It is important for the government to assure that a right investment is made to create appropriate and implementable strategies, plans and programs to ensure the reform initiatives are well accepted by the member in organization. Commitment to change has been recognized as a crucial element to ensure the successful implementation of reform initiatives, including budgetary reform. The purpose of this study is to examine the importance factors (that are communication, participation, transformational and transactional leadership) that influence commitment to change among the OBB focal person in the government ministries in Malaysia. 217 OBB focal person participated in this study via self-administered questionnaires. Multiple regression analysis was employed to analyze the data. The results indicate that all independent variables (i.e. communication, participation, transformational and transactional leadership) were significantly influence employees' commitment to change. Theoretical and practical implications are discussed.